The Effects of Indigo Waste Silage Prepared with Additives on Feed Availability, Rumen Fermentation Patterns, Blood Metabolites, and Hematological Indices in Beef Cattle - Nirawan Gunun; Chatchai Kaewpila; Waroon Khota; Wasana Phlaetita; Pongsatorn Gunun (Veterinary Sciences)
The purpose of this study was to evaluate the impact of different additives in fermented indigo waste on feed availability, rumen fermentation patterns, blood chemistry, and hematology in beef cattle. Four male crossbred beef cattle with a body weight (BW) of 230 ± 14 kg and 25 months of age were used in a 4 × 4 Latin square design. The indigo waste was ensiled without additive (CON) and with calcium hydroxide (CH), molasses (M), or cellulase (C). The indigo waste silage was incorporated into a fermented total mixed ration (FTMR). The neutral detergent fiber (NDF) content was lower in C-treated silage. The feed intake did not alter among treatments (p > 0.05). The ensiled indigo waste with additives had no influence on nutrient digestibility (p > 0.05), whereas the ensiled indigo waste with M increased CP digestibility (p < 0.01). The rumen pH, ammonia-nitrogen (NH3-N), or volatile fatty acid (VFA) proportions did not change by additive (p > 0.05). However, adding M increased the acetate-to-propionate ratio (C2:C3) (p = 0.04). In addition, the total protein in the blood was higher in C-treated silage (p = 0.01). The homological indices did not change by additive (p > 0.05), except for lymphocytes, which decreased when M and C were added (p < 0.01). In conclusion, adding M and C to indigo waste silage could enhance its nutritional value and improve digestibility, blood chemistry, or health status in beef cattle.